The effect of aerosol ipratropium bromide and salbutamol on exercise tolerance in chronic bronchitis. Issue 6 (December 1978) - Leitch, A G; Hopkin, J M; Ellis, D A; Merchant, S; McHardy, G J
Abstract : In a double-blind placebo controlled trial in 24 patients fulfilling the MRC criteria for chronic bronchitis, ipratropium bromide 40 microgram and salbutamol 200 microgram produced similar and significant (P less than 0.001) increases in forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). A greater increase in FEV1 and FVC was seen when both drugs were used together, but this increase did not differ significantly from that produced by either drug alone. Salbutamol increased 12-minute walking distance significantly (P less than 0.001) by 62 +/- 15 metres, whereas the increase of 43 +/- 15 metres observed after ipratropium was not significant (P less than 0.05). With both drugs in combination 12-minute walking distance increased by 72 +/- 15 metres, but this change was not significantly different from that observed with salbutamol alone. If aerosol bronchodilators in the doses used in this study are to be given with a view to improving exercise tolerance in such patients than salbutamol would appear to be the aerosol of choice.